Statistical Analysis of Growth and Amylase Production by Aspergillus flavus grown on Different Carbon Sources (Fountain Journal of Natural and Applied Sciences, 2013)
The mycelial dry weight and dinitrosalicylic acid (D.N.S.A.) method was used to determine growth and amylase production by Aspergillus flavus grown on different carbon sources. Growth of the fungus was determined at 24 h intervals over a period of six days by the dry mycelial weight methods, while the amylase activity in the culture filtrates of A. flavus was determined by the D.N.S.A method. A total of 45 samples were prepared to determine growth and amylase activity of Aspergillus flavus grown on different carbon sources. The concentration of the various carbon sources ranges between 0.4 to 2% W/V. Duncan's multiple range test was used to determine the level of significance of the different carbon sources for effective growth and amylase production by Aspergillus flavus. Aspergillus flavus demonstrated the capability to produce significant growth and amylase activities in the medium containing soluble starch, sorghum and cassava peel as sole carbon source. The amount of mycelial dry weight produced from soluble starch, sorghum and cassava peel is significantly higher than those produced from other carbon sources. The data revealed that there is a correlation between growth and amylase production by Aspergillus flavus. The available data from this study showed that soluble starch is the best carbon source for optimum growth and amylase production by A flavus while sorghum and cassava peel are close substitute for optimum growth and amylase production by Aspergillus flavus.Keywords: Growth, amylase activity and Aspergillus flavus